Visual Processing Assessment on Children: A Pilot Study - Atmarita Atmarita; Syarifuddin Syarifuddin (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2021)
Visual Processing skill plays a key role on how children learn in some areas, such as math, reading, writing and others. This skill supports a child’s self-esteem in the areas of learning. The researcher aims to investigate the visual processing of a children on this age and see how visual processing works on the children. A children of 4.8 years old is the participant of the research. The researcher provide 3 kinds of visual processing assessment: visual discrimination, visual memory/visualization, and visual-motor integration. The first assessment shows that the children in this age recognized and well-discriminated the visual shapes provided. On the second assessment, he memorized where the specific shapes laid on, then he got the correct recognitions. Dealing with visual motor integration, he experienced the first puzzle and reflected on the second puzzle as he did the visual motor integration well. These visual assessments show that the visual processing in children is developing and becoming a significant variables of the children’s preferences of learning physically and mentally.